Facile Access to Twisted Intramolecular Charge‐Transfer Fluorogens Bearing Highly Pretwisted Donor–Acceptor Systems Together with Readily Fine‐Tuned Charge‐Transfer Characters. Issue 20 (7th April 2017) - Luo, Yanju; Wang, Yan; Chen, Shiqi; Wang, Ning; Qi, Yige; Zhang, Xiaogen; Yang, Minghui; Huang, Yan; Li, Ming; Yu, Junsheng; Luo, Daibing; Lu, Zhiyun
Abstract : Twisted intramolecular charge‐transfer (TICT) fluorogens bearing highly pretwisted geometries and readily‐fine‐tuned charge‐transfer characters are quite promising sensor and electroluminescence (EL) materials. In this study, by using 4‐aryloxy‐1, 8‐naphthalimide derivatives as the molecular framework, it is demonstrated for the first time that a CO bond could serve as the central bond to construct new TICT D‐A systems. Photophysical and quantum chemical studies confirm that rotation around central CO bonds is responsible for the formation of a stable TICT state in these compounds. More importantly, owing to the structural adjustability of the aryl moiety and the strong steric interactions between the naphthalimide and the aryl ring systems, these compounds can display readily‐fine‐tuned TICT characters, hence exhibiting an adjustable solvent polarity threshold for aggregation‐induced emission (AIE) activity, and could be AIE‐active even in less‐polar toluene and nonpolar cyclohexane. Furthermore, these compounds could possess highly‐pretwisted ground‐state geometries, hence could show good EL performance. The findings reveal a facile but effective molecular constructive strategy for versatile, high‐performance optoelectronic TICT compounds. Abstract : Using 4‐aryloxy‐1, 8‐naphthalimide as a molecular framework, it is demonstrated for the first time that a CO bond could serve as the central bond to construct twisted intramolecular charge‐transfer (TICT) compounds. More importantly, TICT fluorophores based on this strategy could display both highly‐pretwisted ground‐state geometries and readily‐fine‐tuned TICT strength, leading to adjustable aggregation‐induced emission activity and good electroluminescence performance.